Cylindrical cavity expansion approximations using different constitutive models for the target material. Issue 2 (June 2018) - Johnsen, Joakim; Holmen, Jens Kristian; Warren, Thomas L; Børvik, Tore
In this article, we investigate the results obtained using different constitutive models for the solution of the cylindrical cavity expansion problem under plane strain conditions. The cylindrical cavity expansion solutions are employed with the cylindrical cavity expansion approximation to obtain ballistic limit and residual velocities for ductile metals perforated by rigid projectiles. Many of the previously developed cylindrical cavity expansion approximations use simplified constitutive models. However, in the present work, we first extend the cylindrical cavity expansion theory with the Voce strain hardening rule, before we utilize three different strain hardening constitutive models in cylindrical cavity expansion calculations to predict ballistic limit and residual velocities of aluminum and steel target plates struck by rigid projectiles. The results show that when strain hardening is accurately represented by the constitutive models until necking in a uniaxial tension test, all cylindrical cavity expansion models predict ballistic limit velocities that are close to the experimental data.